Managing multimedia data: a temporal-based approach - Mohd Nordin, Abdul Rahman; Saiful Bahri, Mohamed; Farham, Mohamed; Yuzarimi, M Lazim (2012)
Implement a proper method in multimedia data management is important to support multimedia application’s domain. The method is to ensure that the process of data store, retrieving and manipulation in a distributed environment can be conducted in an efficient manner. A reliable or appropriate format of record structure in multimedia data management tool is required in order to trace validation and transaction of multimedia data. Hence, the concept of temporal database can be applied to overcome this situation. The paper presents the development of the temporal based multimedia data management model. The two elements of time will associate into the model to fulfill the requirement. Transaction time and valid time will monitor the changes (event) and transaction that happen to the multimedia data stored in a database. The use of time elements provided a new schema to query multimedia data based on past, current and future time. The designed model is implemented under web services based environment by utilizing J2EE platform. Applying this implementation approach is believed to provide application sharing under multiple environments, reduce complexity and cost savings.